Sex Education on Islamic Religious Learning To Prevent and Correct Average Behavior In High Schools In Cirebon - Sri Maryati; Muhibbinsyah Muhibbinsyah; Aan Hasanah; Erihadiana Erihadiana (Journal of Social Science, 2021)
This study aims to describe sex education in Islamic religious learning to prevent and overcome deviant behavior at SMAN Cirebon City. This study uses a qualitative approach with a descriptive method. Data collection techniques through interviews, observation and documentation. Data analysis techniques using data analysis techniques consisting of data reduction, data presentation, and conclusions. The results of this study indicate that: in general, students at SMAN in Cirebon City do not all have sufficient knowledge about sexuality. In addition, many of the students still consider it taboo to talk about sexual education. It is a separate task for educators to explain the concept of sexual education. Do not let students actually get information from sources that cannot be accounted for. In overcoming sexual behavior deviations among students at SMAN in Cirebon City, schools play an important role. Some of the roles that schools play in the process of overcoming sexual deviance include (1) providing sex education, (2) providing religious moral education, (3) controlling discipline, (4) becoming consultants and friends for their students.